AKTUALISASI PERAN DEWAN PERS SEBAGAI PENEGAK JURNALISME INDEPENDEN TERKAIT PEMBERANTASAN MEDIA ONLINE ABAL-ABAL - Metha Madonna . (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
In responding to the decelopment of information technology, the Press Council and the Ministry of Communication and informatics formed a Task Force to eradicate cheap online media, but its performance was deemed ineffective even its work definitive wasn’t yet clear. Observation, interview of online media managers, journalists to practitioners who do not understand the role and performance of the Task Force. Don’t even know the team. The reason is the lack of socialization and publication of team formation, there is no urgency so the information is ignored. Qualitative case studies,